Designing Rational Interfacial Bonds for Hierarchical Mineral‐Type Trogtalite with Double Carbon towards Ultra‐Fast Sodium‐Ions Storage Properties. (25th February 2021) - Sun, Wei; Zhao, Wenqing; Yuan, Shaohui; Zhang, Liming; Yang, Yue; Ge, Peng; Ji, Xiaobo
Abstract: Engineering advanced sodium‐ion storage materials with considerable kinetic behaviors have triggered a series of active explorations. However they still suffer from interfacial gaps and uncompleted redox reactions, bringing about poor rate abilities. Herein, through the strategy of salt‐fixed and thermochemical manners, the CoSe2 /OC with interfacial chemical CoOC bonds are successfully prepared, displaying the reduced particles and optimized structural features. Meanwhile, from the analysis of long‐term phase changing curves and ex‐situ technologies, the CoSe2 would be decomposed into CoSe and Se phases but captured by the synergistic effect of their physical‐chemical evolutions, while the structure and new‐type are stabilized after cycling. Profiting from the "bridge" roles of bonds, the electrons are effectively accelerated with the deepening redox reactions. As expected, based on these advantages, the ultra‐fast abilities are reached about 346 mAh g −1 at 15.0 A g −1 after 3500 cycles, and their capacity of full‐cells are also kept at about 326 mAh g −1 (cathodes Na3 V2 (PO4 )3 @C vs anodes CoSe2 /OC). The detailed analysis of kinetic behaviors strongly demonstrated that the increased interfacial charge storage and conductivities are crucial for promoting the ions‐storage abilities. Given this, the rational work is anticipated to provide significant strategies for advanced energy‐storage materials. Abstract : CoSe2 /OC with double carbon is well‐designed through salt‐fixing and thermal‐chemical approaches, displaying the strong interfacial chemical bonds CoOC. Meanwhile, the new‐type phases, CoSe and Se phases from basic CoSe2 can be effectively captured by the advantages of the unique architecture. This work is anticipated to open an avenue for interfacial engineering towards advanced energy storage systems.